Acceptance of mobile loyalty cards in the German B2C consumer goods market - Sandra Schneider (International Journal of Management and Economics, 2021)
The consumer goods market is characterized by strong competition. Thus, to bind customers to the company, a higher priority needs to be attributed to customer retention measures. Such measures include the loyalty card, but the use of the physical card is declining. To counteract this decline, mobile loyalty cards were developed. The basis for the use of mobile loyalty cards is sufficient consumer acceptance. This work is expected to contribute to the explanation of acceptance in the form of usage behavior. Based on the Technology-Acceptance-Model-2 (TAM2) and the literature, hypotheses were derived and a research model was developed. For model testing, a dataset of 255 participants was generated through an online survey and analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that in addition to financial benefits, convenience benefits and psychological factors also have an influence on acceptance. Furthermore, the usage behavior is not negatively influenced by the expected loss of control over personal data. Based on the findings, indications for marketing implementation are given for the confirmed factors.
Keywords: M31; M37; D12; 650; mobile loyalty cards; acceptance; TAM2